Heart rhythm during permanent cardiac pacing. - Edhag, O (1979)
Heart rhythm was analysed with regard to spontaneous or pacemaker-induced heart activity, in a consecutive series of 282 patients paced for at least 1 year. The mean duration of pacing was 59 (13 to 180) months. The mean age of the patients was 76 (39 to 93) years. Spontaneous heart activity at all routine examinations was found in 33 (12%) of the patients. Pacemaker-induced rhythm only was recorded in 42 per cent of the patients whereas the remaining 46 per cent had varying electrocardiographic patterns. Of the patients with spontaneous rhythm at each visit, 10 had had complete heart block before pacing. Regular sinus activity was recorded at every routine examination in 74 per cent of the patients paced for reasons other than the sick sinus syndrome. This indicated that a substantial number of paced patients might be candidates for atrial triggered pacing. Patients treated with digitalis more often had asystole at the time of replacement of the pacemaker (32%) than those not so treated (19). This suggests an increased risk of sudden death in paced patients on digitalis if the pacemaker fails.